Efektivitas Penggunaan LKPD Ditinjau dari Tingkat Percaya Diri Peserta Didik dalam Menyelesaikan Soal HOTS di Kelas X - I Made Surat; I Komang Sukendra; I Dewa Putu Juwana (Journal for Lesson and Learning Studies, 2023)
The low ability of students to solve HOTS questions is caused by a lack of self-confidence as well as exercises provided by the teacher, so in the learning process, students need media that can help their learning process. The purpose of this study was to analyze whether the group worksheet method was more effective than the individual worksheet method in solving questions and whether there was an interaction between the method and students' level of confidence in solving HOTS questions. This type of research is experimental research using a factorial treatment design at level 3x2. The population of this study was all students in class X, totaling 420 children. Sampling in the study was carried out using a double-stage sampling technique. The first stage is to select as many as 3 classes out of 10 existing classes, then determine which classes will be given the treatment of methods A1, A2, and A3. Data collection in the study was carried out using the test method, with the research instrument being a test with HOTS questions. The data obtained were then analyzed using descriptive analysis and factorial analysis. All of these analyses used the SPSS version 22 program. The results of the analysis show that there is a very significant difference between the average group LKPD group and the individual LKPD group, as well as between individual and conventional LKPD groups. Based on these results, it can be concluded that the use of LKPD accompanied by a high level of student confidence can effectively improve students' ability to solve HOTS questions.